Designing a rational sanctioning strategy - Ignazio Angeloni; Christopher Daase; Nicole Deitelhoff; Matthias Goldmann; Jan Pieter Krahnen; Stefan Kroll; Carl-Georg Christoph Luft; Andreas Nölke; Anton Peez; Loriana Pelizzon (Leibniz Institute for Financial Research SAFE, 2022)
This policy note summarizes our assessment of financial sanctions against Russia. We see an increase in sanctions severity starting from (1) the widely discussed SWIFT exclusions, followed by (2) blocking of correspondent banking relationships with Russian banks, including the Central Bank, alongside secondary sanctions, and (3) a full blacklisting of the 'real' export-import flows underlying the financial transactions. We assess option (1) as being less impactful than often believed yet sending a strong signal of EU unity; option (2) as an effective way to isolate the Russian banking system, particularly if secondary sanctions are in place, to avoid workarounds. Option (3) represents possibly the most effective way to apply economic and financial pressure, interrupting trade relationships.
urn:nbn:de:hebis:30:3-634755
Keywords: 330; SWIFT; Russian Sanctions